Fiber profilometer for measurement of hard-to-access areas - Liu, Zhuang (2013)
A fiber profilometer is developed to measure hard-to-access areas. This system utilizes low coherence light interferometry technique to detect profiles of internal surfaces of samples. A differentiation method is employed to enhance vertical resolutions of imaging results. An auto-focusing scheme is proposed to obtain an optimized lateral resolution. The performance of the profilometer system is demonstrated by experimental studies.